Comparison between Accelerated Tests and Natural Exposures for Organic Coating Protective Systems Based on EIS Parameters. Issue 12 (14th December 2021) - Yong, Xingyue; Ji, Haotian; Chen, Zhenning; Ruan, Xin
Abstract : The equivalent relationship between accelerated tests and natural exposures has been extensively studied over the past several years to estimate the service life of a barrier organic coating protective system. Herein, based on the probability density function (PDF) theory, a mathematical expression that describes the limit value of the low-frequency impedance ( R L ) of a barrier organic coating protective system as a function of the elapsed time is proposed in form of Arrhenius formula under certain assumptions, and the degradation coefficient is defined. This expression was consistent with the results of the accelerated tests. The equivalent relationship between accelerated tests and natural exposures, established based on the equivalence principle, was utilized to predict the service life of the coated Al alloy in an ocean atmospheric environment.